Acute respiratory distress syndrome caused by salicylate intoxication. Issue 9 (23rd July 2018) - Otani, Yuichiro; Kanno, Keishi; Toh Yoon, Ezekiel Wong; Tazuma, Susumu
Key Clinical Message: Salicylate‐induced acute respiratory syndrome (ARDS) is a well‐known entity occurring in 35% of salicylate‐intoxicated patient. Careful history taking, physical examination, arterial blood gas analysis, and measurement of serum salicylate concentration will lead to early recognition to initiate appropriate treatment. Abstract : Salicylate‐induced acute respiratory syndrome (ARDS) is a well‐known entity occurring in 35% of salicylate‐intoxicated patient. Careful history taking, physical examination, arterial blood gas analysis, and measurement of serum salicylate concentration will lead to early recognition to initiate appropriate treatment.